The Analysis of Performance-Based Research Fund Principles in the Context of Malaysian Higher Education Institutions - Abd Rahman Ahmad, Siti Norfariza Sunari (International Journal of Advanced Science and Technology, 2020)
Research and Development (R&D) known as one of the important matters for Higher Education Institutions (HEIs) to make each countries’ works well towards technology-driven and national collaboration innovation system. Malaysia is one of the developing countries that hold the aspiration of performance-based research fund (PBRF) that highlighted on outcomes of each research rather than inputs. In Malaysia, apart from the traditional role in teaching and learning, HEIs have increased responsibility to generate new knowledge in the form of research and publications. There wide areas of studies in PBRF and this research focused on the governed principles to be adopted if PBRF is implemented in the Malaysian system. This study adopted a quantitative methodology. The results of this study are expected to give some viewpoints of PBRF principles of analysis through the lens of Malaysian culture towards the same system across other developed countries that already implement it. A study of PBRF at Malaysian public universities should be further explored to analyse the distribution of government research funds to Malaysian public universities and how to explore the PBRF system into Malaysian Higher Education Institutions HEIs.